KEMAMPUAN GURU MATEMATIKA DALAM MENGGUNAKAN KOMPUTER, SMARTPHONE, DAN INTERNET - In In Supianti; Acep Saeful Malik; Anggit Sagita (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2021)
This study aimed to determine the ability of mathematics teachers to use computers, smartphones, and the internet according to their birth years (generation) and gender. The ability of teachers to use computers, smartphones, and the internet is beneficial to support mathematics learning using information and communication technologies. The research method was mixed research by surveying 92 mathematics teachers, 35 junior high school mathematics teachers, and 57 high school mathematics teachers in West Java. The results show that: (1) the ability of mathematics teachers in using computers, smartphones, and the internet has supported the application of technology-based learning in mathematics learning; (2) there are differences in the ability to use computers, smartphones, and the internet among the X, Y and Z generation of mathematics teachers. The ability in using computers, smartphones, and the internet of the Y and Z generation of mathematics teachers is better than that the of X generation; (3) there are differences in the ability in using computers, smartphones, and the internet between male and female teachers; male teachers are better than female teachers; (4) there is no significant difference in the ability in using computers, smartphones and internet between mathematics teachers at the high school and junior high school levels; (5) there is no interaction effect between teacher generations and levels of educational institution, on their achievement of the abilities in using computers, smartphones, and the internet